2021
DOI: 10.1155/2021/8858733
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Fracturing Permeability Characteristics of Cracked Specimens and the Formation Mechanism of Inrush Channel from Floor

Abstract: To study the fracture characteristics and the permeability change law of the cracked specimens during the complete stress-strain process, a mechanical model was constructed, from which different types of crack initiation angles were obtained. The crack inclination angles under uniaxial compression, confining compression, and confining tension, and the influence of confining pressure and pore water pressure on the crack propagation and permeability of rock mass were investigated and simulated with RFPA-Flow sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…The simulation results show that with the increase of water pressure, the confining pressure decreases, while the permeability of the floor increases, and the fractures' penetration and water inrush occur at the stress change position. Wang et al (2021) established a numerical model and analyzed the fracture and hydraulic properties of fractured specimens. It is found that the permeability of floor strata is closely related to the horizontal stress after coal mining, and the longitudinal propagation of wing fractures contributes to the formation of water inrush pathways.…”
Section: Modelling and Numerical Studymentioning
confidence: 99%
“…The simulation results show that with the increase of water pressure, the confining pressure decreases, while the permeability of the floor increases, and the fractures' penetration and water inrush occur at the stress change position. Wang et al (2021) established a numerical model and analyzed the fracture and hydraulic properties of fractured specimens. It is found that the permeability of floor strata is closely related to the horizontal stress after coal mining, and the longitudinal propagation of wing fractures contributes to the formation of water inrush pathways.…”
Section: Modelling and Numerical Studymentioning
confidence: 99%
“…Zhang et al [28] simulated the hydraulic fracturing and studied the evolution law of crack propagation and acoustic emission by RFPAflow. Wang et al [29] used RFPA-flow to study the influence of confining pressure and pore pressure crack propagation and permeability of rock mass under uniaxial compression and, on this basis, analyzed the formation mechanism of floor water inburst channel.…”
Section: Introductionmentioning
confidence: 99%
“…Fractured rock masses are rich in defects of different scales, including pores, microfractures, joints/fractures, and macroscopic discontinuities; the presence of these defects changes the mechanical properties of the rock masses to some extent (deformation modulus and strength parameters are reduced, and the rock masses are anisotropic) and also affects the permeability characteristics of the rock masses [1][2][3]. Along with the increased exploitation of underground space, the geological environment in which the deep rocks are located is special, presenting mechanical characteristics such as high in situ stress, high ground temperature, and high karst water pressure.…”
mentioning
confidence: 99%